CD11c+ T-bet+ CD21hi B Cells Are Negatively Associated With Renal Impairment in Systemic Lupus Erythematosus and Act as a Marker for Nephritis Remission - Sosa-Hernández, Víctor A.; Romero-Ramírez, Sandra; Cervantes-Díaz, Rodrigo; Carrillo-Vázquez, Daniel A.; Navarro-Hernandez, Itze C.; Whittall-García, Laura P.; Absalón-Aguilar, Abdiel; Vargas-Castro, Ana S.; Reyes-Huerta, Raúl F.; Juárez-Vega, Guillermo; Meza-Sánchez, David E.; Ortiz-Navarrete, Vianney; et al. (Frontiers in Immunology, 2022)
Lupus nephritis (LN) is one of the most common manifestations of systemic lupus erythematosus (SLE), characterized by abnormal B cell activation and differentiation to memory or plasma effector cells. However, the role of these cells in the pathogenesis of LN is not fully understood, as well as the effect of induction therapy on B cell subsets, possibly associated with this manifestation, like aged-associated B cells (ABCs). Consequently, we analyzed the molecules defining the ABCs subpopulation (CD11c, T-bet, and CD21) through flow cytometry of blood samples from patients with lupus presenting or not LN, following up a small sub-cohort after six months of induction therapy. The frequency of ABCs resulted higher in LN patients compared to healthy subjects. Unexpectedly, we identified a robust reduction of a CD21hi subset that was almost specific to LN patients. Moreover, several clinical and laboratory lupus features showed strong and significant correlations with this undefined B cell subpopulation. Finally, it was observed that the induction therapy affected not only the frequencies of ABCs and CD21hi subsets but also the phenotype of the CD21hi subset that expressed a higher density of CXCR5. Collectively, our results suggest that ABCs, and more importantly the CD21hi subset, may work to assess therapeutic response since the reduced frequency of CD21hi cells could be associated with the onset of LN.